Proceedings of the 2014 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2014
DOI: 10.3115/v1/d14-1150
|View full text |Cite
|
Sign up to set email alerts
|

Citation-Enhanced Keyphrase Extraction from Research Papers: A Supervised Approach

Abstract: Given the large amounts of online textual documents available these days, e.g., news articles, weblogs, and scientific papers, effective methods for extracting keyphrases, which provide a high-level topic description of a document, are greatly needed. In this paper, we propose a supervised model for keyphrase extraction from research papers, which are embedded in citation networks. To this end, we design novel features based on citation network information and use them in conjunction with traditional features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…However, most of these approaches consider only the textual content of a document or a document's local neighborhood, which is limited to textually-similar documents. In our recent work [3,1], we showed that, in addition to a document's textual content and textually-similar neighbors, other informative neighborhoods exist that have the potential to improve keyphrase extraction. For example, in a scholarly domain, research papers are not isolated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these approaches consider only the textual content of a document or a document's local neighborhood, which is limited to textually-similar documents. In our recent work [3,1], we showed that, in addition to a document's textual content and textually-similar neighbors, other informative neighborhoods exist that have the potential to improve keyphrase extraction. For example, in a scholarly domain, research papers are not isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Our citation context based approaches to keyphrase extraction [3,1] outperform many existing unsupervised (e.g., TextRank [8] and ExpandRank [9]) and supervised (e.g., Hulth's [5] and KEA [2]) approaches. However, a comparison with the approach by Medelyan et al [7], called Maui, was not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Chuang et al (2012) proposed a model that incorporates a set of statistical and linguistic features (e.g., tf-idf, BM25, part-of-speech filters) for identifying descriptive terms in a text. Caragea et al (2014a) designed features based on information available in a document network (such as a citation network) and used them with traditional features in a supervised framework.…”
Section: Related Workmentioning
confidence: 99%
“…keyphrases and key sentences, is relevant to our problem. There are two types of extraction, i.e., supervised [2], [6], [7], [9] and unsupervised methods [1], [3], [4], [8], [10], [11]. Natural language processing techniques [12], [13], [14] have also been used for keyphrase extraction.…”
Section: Related Workmentioning
confidence: 99%